Alkynyl-functionalization of hydroxypropyl cellulose and thermoresponsive hydrogel thereof prepared with P(NIPAAm-co-HEMAPCL). (10th February 2016) - Miao, Lei; Hu, Jiwen; Lu, Mangeng; Tu, Yuanyuan; Chen, Xin; Li, Yinwen; Lin, Shudong; Li, Fei; Hu, Shengyu
Highlights: Hydroxypropyl cellulose was modified with alkynyl as a crosslinker. High response rate and well compressive strength of the hydrogel. The swelling–deswelling and compressive properties can be adjusted. Heterogeneous and semicontinuous internal structures of the hydrogel. Abstract: A ternary system thermoresponsive hydrogel, poly( N -isopropylacrylamide- co -hydroxyethyl methylacrylate polycaprolactone)/hydroxypropyl cellulose (or P(NIPAAm- co -HEMAPCL)/HPC), was prepared via "alkynyl/azide" click chemistry between the azide modified graft copolymer P(NIPAAm- co -HEMAPCL-N3 ) and the alkynyl modified HPC (or alkynyl-HPC). The structures of P(NIPAAm- co -HEMAPCL-N3 ) and alkynyl-HPC were characterized by 1 H NMR, SEC and FT-IR, and the results demonstrated that the mole ratio of the alkynyl and azide functional groups, and the feed ratios of HPC, PCL, and PNIPAAm could be easily adjusted. The incorporation of PCL and HPC dramatically enhanced the compression modulus of the P(NIPAAm- co -HEMAPCL)/HPC hydrogel, which ranged from 500 to 1000 g/cm 2 . Due to the immiscibility of HPC and PCL, a heterogeneous and semicontinuous structure was observed via SEM. The incorporation of HPC accelerated the water absorption rate and enhanced the hydrogel's ability to shed water. The swelling–deswelling and compressive properties could also be adjusted by changing the feeding ratio. The hydrogel exhibited reversible swelling–deswelling behavior after three "swelling–deswelling" cycles.